2020
DOI: 10.1177/0300060520969494
|View full text |Cite
|
Sign up to set email alerts
|

Successful secukinumab treatment of erythrodermic psoriasis and psoriatic arthritis concomitant with severe noninfectious uveitis: a case report

Abstract: Uveitis is considered a relatively rare but serious ocular complication of psoriasis. We report the first successful treatment of severe noninfectious uveitis with secukinumab in a 70-year-old woman with erythrodermic psoriasis and psoriatic arthritis. Anti-tumor necrosis factor (TNF) agents were administered for 5 years for the treatment of erythrodermic psoriasis and psoriatic arthritis. Although the symptoms improved, she later developed noninfectious uveitis, resulting in a sharp decline in vision. After s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…21 This article reviews the literature on the successful treatment of EP with secukinumab (Table 1). Patients who did not respond well to other biological agents or traditional treatments or patients with other serious diseases such as end-stage renal disease, noninfectious uveitis, and HIV are included in Table 1, 3,22,23 indicating that secukinumab may be a viable option for patients with EP who do not respond to other treatments and have severe comorbidities. 24 However, the National Psoriasis Foundation's guideline for the use of biologics in EP, published in 2019, recommends that secukinumab be characterized only as a "grade C" recommendation for treating EP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 This article reviews the literature on the successful treatment of EP with secukinumab (Table 1). Patients who did not respond well to other biological agents or traditional treatments or patients with other serious diseases such as end-stage renal disease, noninfectious uveitis, and HIV are included in Table 1, 3,22,23 indicating that secukinumab may be a viable option for patients with EP who do not respond to other treatments and have severe comorbidities. 24 However, the National Psoriasis Foundation's guideline for the use of biologics in EP, published in 2019, recommends that secukinumab be characterized only as a "grade C" recommendation for treating EP.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrodermic psoriasis (EP) is an uncommon and severe form of psoriasis characterized by generalized scaly erythema involving more than 75% of the body surface area, with numerous complications and a high mortality rate 1 . Currently, the safety and efficacy of secukinumab for the treatment of EP have been confirmed, with several reports of successful treatment in adult EP, 2,3 while there is only one reported successful EP treatment using secukinumab in children 4 . Herein, we present a case of vaccine‐induced EP in a 7‐year‐old boy successfully treated with secukinumab combined with symptomatic therapy and supportive care, as well as a brief literature review of the disease.…”
Section: Introductionmentioning
confidence: 89%
“…83 Its use in the management of EP has been reported in several case series [27][28][29][30][31][32] and case reports. [33][34][35][36][37][38]84 However, there are no clinical trials available. The largest case series has been reported by Damiani et al who reported the results of a multi-center, international, retrospective, pilot study enrolling 13 EP patients receiving secukinumab for 52 weeks.…”
Section: Secukinumabmentioning
confidence: 99%
“…T17 cells play a key role in sustaining the inflammatory cascade in psoriasis. Secukinumab was the first IL-17A inhibitor to emerge as one of the preferred biological agents to manage chronic psoriasis in patients with multiple comorbidities, including uveitis (36). Notably, ustekinumab has also demonstrated good results in uveitis (37).…”
Section: Ophthalmological Changesmentioning
confidence: 99%